NUTRITIONAL AND ANTIOXIDANT POTENTIAL OF LYOPHILIZED WHEAT GRASS JUICE AND SHOOT POWDERS - N.M. JABEEN*, POOJA YADAV, MAHADEVA NAIKA, MALLESHA and N. DEVANNA, (The Journal of Research ANGRAU, 2020)
Young wheatgrass is rich in vitamins, minerals, chlorophyll, bioactive compounds, and fiber. In thisstudy, phytochemicals, proximate analysis, amino acids, individual polyphenols, minerals, and antioxidantsof lyophilized wheatgrass juice powder and shoot powder were estimated. Both the samples (juice and shootpowders) showed the presence of phytochemicals such as alkaloids, tannins, cardio-glycosides, coumarins,flavonoids, carbohydrates, etc. Further more, HPLC analysis of individual polyphenols showed that the juicepowder had significantly higher (P